2011
DOI: 10.1016/j.cognition.2010.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating explanations in relative clause processing

Abstract: We show that comprehenders’ expectations about upcoming discourse coherence relations influence the resolution of local structural ambiguity. We employ cases in which two clauses share both a syntactic relationship and a discourse relationship, and hence in which syntactic and discourse processing might be expected to interact. An off-line sentence-completion study and an on-line self-paced reading study examined readers’ expectations for high/low relative clause attachments following implicit-causality and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 49 publications
1
54
0
1
Order By: Relevance
“…For example, contextual information can lead to facilitated processing of incoming information at the level of syntactic structure (see previous section, and Arai & Keller, 2013; Farmer, Christiansen, & Monaghan, 2006; Garnsey et al, 1997; Gibson & Wu, 2013;Hare et al, 2003; Rohde, Levy, & Kehler, 2011; Tanenhaus, Spivey-Knowlton, Eberhard, & Sedivy, 1995; Wilson & Garnsey, 2009), phonological information (Allopenna, Magnuson, & Tanenhaus, 1998; DeLong et al, 2005) and orthographic information (DeLong et al, 2005;Dikker, Rabagliati, Farmer, & Pylkkänen, 2010). …”
Section: Section 2: Using Different Types Of Information Within a Conmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, contextual information can lead to facilitated processing of incoming information at the level of syntactic structure (see previous section, and Arai & Keller, 2013; Farmer, Christiansen, & Monaghan, 2006; Garnsey et al, 1997; Gibson & Wu, 2013;Hare et al, 2003; Rohde, Levy, & Kehler, 2011; Tanenhaus, Spivey-Knowlton, Eberhard, & Sedivy, 1995; Wilson & Garnsey, 2009), phonological information (Allopenna, Magnuson, & Tanenhaus, 1998; DeLong et al, 2005) and orthographic information (DeLong et al, 2005;Dikker, Rabagliati, Farmer, & Pylkkänen, 2010). …”
Section: Section 2: Using Different Types Of Information Within a Conmentioning
confidence: 99%
“…For example, to facilitate semantic processing of new information, comprehenders are able to use information within a verbal context about specific discourse connectives (Rohde & Horton, 2014; Xiang & Kuperberg, 2015), inferential causal relationships (Kuperberg et al, 2011), the selection restrictions of a verb (Altmann & Kamide, 1999; Paczynski & Kuperberg, 2012), the tense of a preceding verb (Altmann & Kamide, 2007), the combination of a specific verb and argument (Kamide et al, 2003; Matsuki et al, 2011; Metusalem et al, 2012; Paczynski & Kuperberg, 2012), pre-verbal arguments (Bornkessel-Schlesewsky & Schlesewsky, 2009; Kamide et al, 2003), specific prepositions (Chambers et al, 2002), and prosody (Kurumada, Brown, Bibyk, Pontillo, & Tanenhaus, 2014; Snedeker & Yuan, 2008). Similarly, to facilitate the processing of new information at the level of syntactic structure, comprehenders can use information within a verbal context about its referential discourse structure (Gibson & Wu, 2013), discourse coherence relationships (Rohde et al, 2011), thematic relationships between verbs and arguments (Garnsey et al, 1997; Wilson & Garnsey, 2009), the specific sense of a verb (Hare et al, 2003), or even their knowledge about a verb’s phonological typicality (Farmer et al, 2006). There is also evidence that syntactic information within a context can facilitate the processing of orthographic information (Dikker et al, 2010) or even low level perceptual features (Dikker, Rabagliati, & Pylkkänen, 2009).…”
Section: Section 2: Using Different Types Of Information Within a Conmentioning
confidence: 99%
“…(which signals an Occasion relation, which is biased to the Goal). Finally, Rohde, Levy & Kehler (2011) showed that the expectations that object-biased IC verbs create for an ensuing Explanation, along with the next-mention biases toward their direct objects, influence syntactic attachment biases in online relative clause processing.…”
Section: Hementioning
confidence: 99%
“…Rohde, Levy, and Kehler (2011) provided experimental evidence that discourse coherence relationships such as Causal and Contiguity relationships play roles in the interpretation and processing of relative clauses, and Rohde & Kehler (2009) explicitly recognized the relation between discourse coherence relationships and QUDs…”
mentioning
confidence: 99%